Geopolitics, military modernisation and the future of the Indo-Pacific - Gill, Bates 1959-; Lockyer, Adam; Lim, Yves-Heng 1979-; Tan, Andrew T. H. 1961- (Routledge, Taylor & Francis Group, 2025)
"This book examines to what extent geopolitics explains the current wave of force modernisation in the Indo-Pacific region. Examining the leading Indo-Pacific nations in terms of defence spending: the United States, China, India, Japan, South Korea, Australia, Taiwan, Singapore, Pakistan, Indonesia and Thailand, geopolitical principles are used to create hypotheses that can be tested against the military modernisation programs of the major actors in the Indo-Pacific region. The book represents a bridge between reference works and the literature on international politics in the Indo-Pacific. The empirical chapters provide qualitative narratives that explore the force postures, military modernisation and procurement patterns of the cases and assess why these nation's military modernisation have followed particular courses and evaluate this evidence against the expectations of geopolitics and its rivals. This book will be a valuable addition to scholars, practitioners and, indeed, anyone interested in the future stability of one of the world's most important and dynamic regions"
Keywords: Geopolitik; Militärpolitik; Indopazifik; Indo-Pacific Region / Defenses; Military planning / Indo-Pacific Region; Geopolitics / Indo-Pacific Region; Security, International / Indo-Pacific Region; Military readiness